Crown Princes and Benjamins: Birth Order and Educational Attainment in East and West Germany - Martina Eschelbach (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2009)
This study expands the literature on the determinants of educational attainment by analyzing the effects of birth order in Germany. These effects are typically attributed to sibling rivalry for parental resources. Using data from the German Life History Study on birth cohorts 1945-1978, we find highly significant effects of birth order on secondary education. The effects are of substantial magnitude, both in West and East Germany. To our knowledge, this is the first study that also examines possible trends in the birth order effects. In West Germany, the effects remained stable over time, whereas in East Germany, the disadvantage for later born children increased. The result for East Germany is surprising because, during the period of the analysis, the care and education of preschool children was more and more shifted from parents to state run institutions, where the treatment of children should have been independent of birth order.
Keywords: I21; J13; 330; birth order; sibling configuration; educational attainment; East and West Germany; gender differences